Differential effects of HIV infected macrophages on dorsal root ganglia neurons and axons - Hahn, Katrin (2007)
Human immunodeficiency virus-associated distal-symmetric neuropathy (HIV-DSP) is the most common neurological complication of HIV infection. The pathophysiology of HIV-DSP is poorly understood and no treatment is available for this entity. The dorsal root ganglia (DRG) are the principal sites of neuronal damage and are associated with reactive mononuclear phagocytes as well as HIV-infected macrophages. To determine the role of HIV-infected macrophages in the pathogenesis of HIV-DSP, we developed a technique for culturing human DRG’s. When the dissociated DRG neurons were exposed to supernatants from macrophages infected with CXCR4 or CCR5 tropic HIV-1 strains axonal retraction was observed without neuronal cell death but there was mitochondrial dysfunction in the neuronal cell body. Even though CXCR4 and CCR5 were expressed on the DRG neurons, the effects were independent of these receptors. Antioxidants rescued the neuronal cell body but not the axon from the toxic effects of the culture supernatants. Further, peripheral nerves of HIV-infected patients obtained at autopsy did not show evidence of increased oxidative stress. These observations suggest a differential effect on the axon and cell body. Different mechanisms of injury may be operative in these two structures.